OSTEOPOROSIS PADA WANITA POSTMENOPOUSE Sri Kentjananingsih (Lentera, Jurnal Studi Perempuan, 2010)
Abstract Osteoporosis is ihe loss ofbone that reduce our physical cictivity and our healthy. It is slowly happened in seni le without cmy prominent change symptoms. Once he/she suffered from a non signifcantly cansal fracture. We kecn on knowing, whether all senile persons su ffered from osteoporosis ? Why does it prominent happen in postmenopausal women ? How does it in men ? In young adu/1 ? A re calcium contain products efjective in inhibiting this condition ? According to Cmy ton (J 996) 4% ofall osteoblasts are active in living bone and active osteoclasts are always lied on I % ofthe bone surface during our life time. The changing ofthe growth hormone concentration makes the changing of osteoblasts and osteoclasts activity balance during our life period. The peak ofthe bone density is reached a t the age of 30 (Saladi n, KS. and Poli e, C K. 1998). and actually fat person have denscr bone that slim person (Guytcfn- 1996). After that age. the bone mass is decreasing for about 8% in women and 3 % in men per decade (Guyton-1996) The decreasing bone density depends on their general healthy; consumed nutrition, sex hormone. insulin, calcitonin. and thyroid hormones, the Ca-P metabolism balance, and stresses on the bone. (Guyton 1996). A pre clinical research especially on postmenopausal women w as donefrom 1993-1996. The re suit: the re w e re 33 healthy postmenopausal women or 0.038 % ofall visitor patients that were not suffered from osteoporosis. They were 44- 66yectrs oldwith the mean of52.73years, the mode 47years. They had l-9years menopause, with the mean of 5,73 years, the mode 1 yecir. Their age range of menopause onsetis between 38-62years, with the mean of47,24year, the mode of 48 vear. Actually they are in middle to low social level; Their aetivities postpone the onset of osteoporosis. It is prominent in postmenopausal women because estrogen almost los t from their blood. Men may be the vietim, but it happened slower. Young age may also be ihe vietim because of several influencing faetors. Not all calcium products are effective in inhibiting osteoporosis. It importcint that w e consult to our physicictns to get the bestforyou. Keywords : osteoporosis. postmenopause